A new strategy and fewer forces. Executive summary : the Pacific dimension - Winnefeld, James A., 1929-; Pollack, Jonathan D.; Lewis, Kevin N. (Kevin Neil), 1955-; Pullen, L. D.; Schrader, John Y.; Swaine, Michael D., 1951-; Rand eBooks (Santa Monica, CA : RAND, 1992)
This report considers how the United States should reposture its forces, adjust its policies, and change its military operations in the Asia-Pacific region, all in the context of reduced resources and increased burden-sharing by allies and security partners. It assesses six alternative U.S. regional force postures that might develop over the next 15 years. Each posture is examined for the regional responses it might evoke, its performance in a variety of future contingencies, and its comparative cost. The report identifies five factors that will shape Asia's future and America's role in it: (1) the implosion of Soviet power and its political and security consequences, (2) the development of Japan as a global economic and technological power, (3) the primacy of economics in both domestic and international contexts, (4) the unsettled political and economic futures of the Asian communist regimes, and (5) the reconfiguration of America's regional alliances in the context of rapid domestic political change. The authors list several policy and program initiatives designed to mitigate the potential negative effects of U.S. force posture reductions.
Research "developed by the staff of the RAND Strategy Assessment Center ... part of RAND's National Defense Research Institute"--Preface.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Asia -- Defenses; Pacific Area -- Defenses; United States -- Armed Forces -- Asia; United States -- Armed Forces -- Pacific Area; Electronic books